Strategi Pemberdayaan UMKM Sektor Peternakan Ayam Organik (StudiPadaKoperasi Hidayah Sumatera Utara) - Latief Ilhamy; Sundari Pratiwi (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2018)
MSME (Micro, Small and Medium Enterprises) is one of the efforts that have the Indonesian government to reduce unemployment , poverty and income distribution . In Indonesia, SMEs dominate as much as 99 % ( percent ) and 1% for large businesses . SMEs have also been able to absorb significant workforce that is as much as 97 % . SME sector is also able to contribute around 56% of gross domestic product . For that I am interested in studying the issues related to SMEs SME sector is an organic chicken farm in Medan that is empowered by the Cooperative Hidayah SU . This research aims to ( 1 ) the role of cooperatives Untukmengetahui guidance to the SMEs sector in the field of organic chicken farms . ( 2 ) To determine what factors are causing failures organic chicken farm in Medan . ( 3 ) What steps are performed Cooperative Hidayah Medan in addressing the failure of the organic chicken farm.